2014
DOI: 10.1093/carcin/bgu019
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin prevents ATP-driven invasiveness via P2X7 and EHBP1 signaling in PTEN-expressing prostate cancer cells

Abstract: Epidemiological studies indicate that statins, cholesterol-lowering drugs, prevent aggressive prostate cancer and other types of cancer. Employing essentially non-prostate cell lines, we previously showed that statins rapidly downregulate nuclear levels of phosphorylated Akt via P2X7, a purinergic receptor recently implicated in invasive growth. Here, we present studies on phosphatase and tensin homolog deleted on chromosome 10 (PTEN)-positive prostatic cells. We document an involvement of EH domain-binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 45 publications
2
61
0
1
Order By: Relevance
“…In tumor cells, P2X7R is constantly and tonically active, thus causing: (i) moderate increase in the endoplasmic reticulum and mitochondrial Ca 2þ concentration; (ii) enhanced efficiency of oxidative phosphorylation; (iii) increase in intracellular ATP stores; (iv) activation of the transcription factor NFATc1; (v) stimulation of aerobic glycolysis; and (vi) stimulation of proliferation (5,38,40,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…In tumor cells, P2X7R is constantly and tonically active, thus causing: (i) moderate increase in the endoplasmic reticulum and mitochondrial Ca 2þ concentration; (ii) enhanced efficiency of oxidative phosphorylation; (iii) increase in intracellular ATP stores; (iv) activation of the transcription factor NFATc1; (v) stimulation of aerobic glycolysis; and (vi) stimulation of proliferation (5,38,40,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is one of the key regulation factors in the process of DNA repair and the expression is then increased in order for it to participate in the process of cancer development (26,27). In previous studies, PTEN was tested in PCa and hyperplastic prostate tissues, and it was observed to be mainly expressed in PCa tissues and in the cell nuclei of hyperplastic prostate tissues (28,29). The expression of PTEN in PCa was significantly higher than that in prostate hyperplasia, which indicated that increased PTEN expression levels may be associated with the incidence of PCa (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the up-regulation of P2X 7 in prostate cancer observed by other groups [39], the receptor is expressed at high level in its nonfunctional form [15,40], an example of which involved the E496A mutant [41], a mutation found to produce a loss of pore functionality [42]. Additional confirmations, many very recently, of the up-regulation of the receptor in cancer tissue have been obtained for pancreatic [43], lung [44], skin [45][46][47], brain [48,49], renal [38], prostate [50], thyroid [51], bone [52] and both ALL and AML [53,54].…”
Section: Discussionmentioning
confidence: 94%